Supercapacitors: Review (Research, Society and Development, 2022)
It is known that in an energy conversion and storage device, having high power density and remarkable durability are characteristics of great relevance. The supercapacitor (SC) has these two characteristics, however, it is still necessary to face challenges during the fabrication and management of the SC. Therefore, the study of new materials to fill these gaps in this device is necessary. Thus, the objective of this work was to discuss the working principles of different materials – such as metallic oxides, intrinsically conductive polymers and carbon-based materials – with the potential to produce more efficient supercapacitors. These will be addressed from both a research and an application point of view, along with their properties, specific area and capacitance. In addition, industrial applications described in the literature are also discussed in order to qualitatively and quantitatively assess recent research progress and encourage innovations in SC control and management.